2007
DOI: 10.1021/ja075711c
|View full text |Cite
|
Sign up to set email alerts
|

DNA as Supramolecular Scaffold for Porphyrin Arrays on the Nanometer Scale

Abstract: Tetraphenyl porphyrin substituted deoxyuridine was used as a building block to create discrete multiporphyrin arrays via site specific incorporation into DNA. The successful covalent attachment of up to 11 tetraphenyl porphyrins in a row onto DNA shows that there is virtually no limitation in the amount of substituents, and the porphyrin arrays thus obtained reach the nanometer scale (approximately 10 nm). The porphyrin substituents are located in the major groove of the dsDNA and destabilize the duplex by del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
167
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(176 citation statements)
references
References 97 publications
6
167
0
2
Order By: Relevance
“…Recently, the synthesis of a DNA containing eleven meso-functionalized porphyrins attached to 5-ethynyl-2'-deoxyuridines was carried out from the corresponding phosphoramidites; however, this showed a significant thermal destabilization of the resulting duplex. [6] A stabilizing effect of +0.5 8C per modification was observed when the porphyrins were placed adjacent in complementary strands. [7] Molecular modelling showed that the porphyrins were arranged in a zigzag fashion and stacked in pairs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the synthesis of a DNA containing eleven meso-functionalized porphyrins attached to 5-ethynyl-2'-deoxyuridines was carried out from the corresponding phosphoramidites; however, this showed a significant thermal destabilization of the resulting duplex. [6] A stabilizing effect of +0.5 8C per modification was observed when the porphyrins were placed adjacent in complementary strands. [7] Molecular modelling showed that the porphyrins were arranged in a zigzag fashion and stacked in pairs.…”
mentioning
confidence: 99%
“…[4] Covalent attachment of porphyrin moieties to DNA has been achieved by using a variety of methodologies, including: the modification of nucleobases, [5][6][7][8] ribofuranose residues, [9][10][11][12][13] phosphate backbone [14][15][16] and by using acyclic linkers. [17,18] This provides structures that have porphyrin residues as 3'-or 5'-molecular caps, [12,[18][19][20] thus introducing them instead of a nucleobase in the middle of the helix [17] or as a label in the minor [10,16] and major [6][7][8] grooves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since our initial proposal to use DNA as a scaffold for porphyrin arrays [4] as compared to noncovalent assemblies, [5] we have studied both tetraphenylporphyrin (TPP) and diphenylporphyrin (DPP)-substituted DNA [6] and found significant differences in the thermal stability and the electronic properties of the multiporphyrin systems. [7,8] The attachment of substituents on one strand has an especially profound impact on the stability of the DNA duplex. In contrast to this one-strand modification, individual porphyrins, [9,10] metal-chelating ligands, [11] and pyrene-perylene systems [12] have been attached to both complementary strands, which leads to new supramolecular systems after hybridization.…”
mentioning
confidence: 99%
“…[17] As we know from previously synthesized strands, the attachment of TPP in 2 onto one DNA strand leads to a decrease in the T m of DT m = À13.5 8C for three porphyrins, or DT m = À34.1 8C for eleven porphyrins compared to the corresponding natural DNA strand in a 21 base-pair (bp) sequence. [8] The zipper array 4 b·5 b, incorporating three stacked TPP moieties after hybridization, displays DT m = À4.1 8C, that is, an effective DT m of + 9.4 8C for the zipper in comparison with the one-strand porphyrin-DNA. The effect is even more remarkable in the duplex 6 b·7 b.…”
mentioning
confidence: 99%